2nd Edition of Integrated Human Exposure to Air Pollution (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This reprint, entitled "Second Edition of Integrated Human Exposure to Air Pollution", presents new insights into key aspects of human exposure to air pollution. It compiles seventeen innovative studies, exploring five main areas: advanced methodologies for exposure assessment, citizen engagement in addressing pollution, outdoor air pollution, indoor air quality, and the health impacts of pollution. Notably, the reprint features two comprehensive reviews, one on the effects of climate change on indoor air and another on the health impacts of long- and short-term exposure to NO2 and PM2.5.